2016
DOI: 10.1016/j.envres.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bisphenol A is associated with dysregulation of HPA-axis function in pregnant women: Findings from the APrON cohort study

Abstract: These findings provide the first human evidence suggesting that BPA exposure is associated with dysregulation of HPA-axis function during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…A complete description of the methods for detecting total BPA in the current samples was reported previously [21]. Briefly, urinary total BPA concentrations were quantified by online solid-phase extraction coupled to high performance liquid chromatography and an Orbitrap Elite hybrid mass spectrometer (Thermo Fisher Scientific, San Jose, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A complete description of the methods for detecting total BPA in the current samples was reported previously [21]. Briefly, urinary total BPA concentrations were quantified by online solid-phase extraction coupled to high performance liquid chromatography and an Orbitrap Elite hybrid mass spectrometer (Thermo Fisher Scientific, San Jose, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our research group published the first human data on the association between maternal urinary total BPA concentrations and HPA axis function [21]. This study discovered an association between BPA exposure and dysregulation of the maternal HPA axis.…”
Section: Introductionmentioning
confidence: 99%
“…High u-BPA levels in the second trimester of pregnancy were associated with disturbed cortisol circadian rhythm with suppressed morning and day-time levels of saliva cortisol [75]. In adults, a Czech study of fertile and infertile men (n=191) found a positive correlation between plasma BPA levels 24 and the ratio of plasma cortisol/cortisone ratio [76].…”
Section: Human Studies: Associations Between Bpa Exposure and Cortisomentioning
confidence: 99%
“…3.6.6 Foetal exposure: programming and epigenetics 3.6.6.1 Prenatal exposure Pregnant Sprague-Dawley rats were administered a single dose of genistein by gavage (20,34,75 mg genistein/kg bw) at gestational day 20. Two hours later, conjugated genistein and genistein aglycone was detected in foetal circulation (70% and 30%, respectively) and in foetal brain (10% and 90%, respectively) [298].…”
Section: The Hpg-axismentioning
confidence: 99%
“…It has been widely used in food cans, plastic bottles and other consumer products leading to nearly ubiquitous human exposure [15]. In silica research indicates BPA is a glucocorticoid receptor agonist [16], and it has been associated with altered HPA axis function in juvenile trout [17] and pregnant women [18]. During pregnancy, surges in glucocorticoid levels are essential for normal maturation of several organ systems, however, elevated glucocorticoids at incorrect developmental stages have been shown to disrupt fetal programming of the HPA axis [19, 20].…”
Section: Mechanism 1: Disrupted Hpa Axis Functionmentioning
confidence: 99%